Positive electrode active material and preparation method thereof, positive electrode sheet, battery and electrical equipment

By increasing the oxidation conversion of Fe2+ in the positive electrode active material of sodium ion batteries, the problem of insufficient energy density of NaxMO2 materials is solved, and higher energy density and lower material cost are achieved.

CN118645618BActive Publication Date: 2025-04-18BEIJING EASPRING MATERIAL TECH CO LTD

Patent Information

Application Number
CN202410869502.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-04-18
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

NaxMO2 material has problems such as insufficient energy density and high material watt-hour cost in sodium ion batteries, which require increasing energy density and reducing costs.

Method used

A positive electrode active material is proposed, whose Fe2+ content varies Δn≥0.1 during charging to 4.0V, and more electrons are transferred through Fe2+/Fe3+ oxidation reaction, thereby improving material capacity and battery energy density.

Benefits of technology

By increasing the oxidation conversion of Fe2+, the capacity of the positive electrode active material and the energy density of the battery containing the material are improved, and the problem of insufficient energy density is solved, while reducing the watt-hour cost of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118645618B_ABST
    Figure CN118645618B_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electric device, and relates to the technical field of batteries. The positive electrode active material, Fe in the positive electrode active material 2+ The change in content Δn≥0.1, Δn=n1-n2; wherein n1 is the Fe content in the positive electrode active material before charging. 2+ n2 is charged to 4.0V, the positive electrode active material Fe 2+ Content: Fe 2+ Content = Fe in positive electrode active material 2+ Amount of substance / (Fe in positive electrode active material 2+ Amount of substance + Fe in positive electrode active material 3+ Thus, by using the positive electrode active material, the battery loaded with the positive electrode active material can have excellent energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and in particular relates to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art

[0002] In recent years, lithium-ion batteries have developed rapidly and are widely used in new energy vehicles, energy storage power stations, and digital 3C products. However, the price of lithium resources fluctuates greatly with market conditions. In the current industry context, sodium-ion batteries, with their abundant sodium resources and low prices, have the same working mechanism as lithium-ion batteries, can significantly reduce battery manufacturing costs, and are expected to be widely used in low-speed electric vehicles and energy storage fields.

[0003] In the sodium ion battery system, the cathode materials are mainly divided into three types: layered oxides, polyanions and Prussian blue. x MO2) materials, with their advantages of high energy density, good low-temperature performance, simple process and easy large-scale production, have been first used in the markets of mid- and low-end passenger vehicles, energy storage systems, etc.

[0004] However, as lithium prices fall, Na x MO2 materials are gradually losing their cost advantage and are in urgent need of further improving energy density and reducing material watt-hour costs. x Due to the shortcomings of MO2 materials, improving the energy density of the materials has become a topic to be studied and solved in this invention. Summary of the invention

[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electric device, wherein the positive electrode active material has a high capacity so that the battery containing the positive electrode active material has an excellent energy density.

[0006] In one aspect of the present invention, the present invention provides a positive electrode active material, wherein Fe 2+ The change in content Δn≥0.1, Δn=n1-n2; wherein n1 is the Fe content in the positive electrode active material before charging. 2+ n2 is charged to 4.0V, the positive electrode active material Fe 2+ Content: Fe 2+ Content = Fe in positive electrode active material 2+ Amount of substance / (Fe in positive electrode active material 2+ Amount of substance + Fe in positive electrode active material 3+ amount of substance).

[0007] The positive electrode active material according to an embodiment of the present invention, during charging to 4.0 V, the change Δn in the content of Fe 2+ is ≥ 0.1, such that more Fe 2+ is converted into Fe 3+ , and the large change in the content of Fe 2+ allows more electrons to be transferred during the charging process, improving the capacity of the positive electrode active material, and thus enhancing the energy density of the battery containing the same.

[0008] In addition, the positive electrode active material according to the above embodiment of the present invention may further have the following additional technical features:

[0009] In some embodiments of the present invention, Δn ≥ 0.15.

[0010] In some embodiments of the present invention, n1 is greater than 50%; preferably, n1 is greater than 70%; more preferably, n1 is greater than 80%.

[0011] In some embodiments of the present invention, the positive electrode active material includes:

[0012] Na a1 Ni x1 Fe y1 Mn z1 Zn m1 Ca q M p1 O2,

[0013] wherein, 0.90 ≤ a1 ≤ 1.10, 0 < x1 ≤ 0.5, 0 < y1 ≤ 0.5, 0 < z1 ≤ 0.5, 0 < m1 ≤ 0.1, 0 ≤ q ≤ 0.05, 0 < p1 ≤ 0.05;

[0014] M includes at least one of Cu, Ti, Mg, Sr, Sn, Sb, Zr, Nb, Y, W, and La.

[0015] In some embodiments of the present invention, a1:(x1 + y1 + z1 + m1 + q + p1) = (0.90 - 1.05):1, preferably (0.95 - 1.05):1; more preferably (0.97 - 1.03):1.

[0016] In some embodiments of the present invention, 0.01 < m1 ≤ 0.1, preferably 0.05 < m1 ≤ 0.1.

[0017] In some embodiments of the present invention, 0.01 < q ≤ 0.05.

[0018] In some embodiments of the present invention, the ionic radius r of M > 0.06 nm.

[0019] In some embodiments of the present invention, the positive electrode active material is an O3 type sodium ion battery layered oxide.

[0020] In some embodiments of the present invention, the D of the positive electrode active material 50 The particle size is 3μm-12μm, preferably 4μm-10μm; more preferably 5μm-8um.

[0021] In some embodiments of the present invention, the particle size distribution of the positive electrode active material is 1.1 < (D 90 -D 10 ) / D 50 <1.6, preferably 1.2<(D 90 -D 10 ) / D 50 <1.4.

[0022] In a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned positive electrode active material, comprising:

[0023] A Na source, a cathode active material precursor, an optional Zn source, an optional Ca source, and an M source are mixed uniformly according to a stoichiometric ratio to obtain a mixed material, wherein the cathode active material precursor includes Fe;

[0024] The mixed material is calcined in an oxidizing atmosphere, crushed and sieved to obtain a positive electrode active material.

[0025] Thus, the above-mentioned positive electrode active material can be prepared by this method, and Zn is added to the layered oxide of the sodium ion battery, and the initial Fe 2+ Higher, which is conducive to the passage of Fe during charging 2+ / Fe 3+ The oxidation reaction transfers more electrons, providing more capacity, thereby increasing the energy density of the battery.

[0026] In some embodiments of the present invention, the ratio of the amount of substance of the Na element to the sum of the amounts of substance of Ni, Fe, Mn, Zn, Ca and M is 0.90-1.10, preferably 0.97-1.03.

[0027] In some embodiments of the present invention, the calcination temperature is 900°C-1100°C.

[0028] In some embodiments of the present invention, the calcination includes a first heating stage, a second heating stage and a heat preservation stage, and the difference between the heating rate of the first heating stage and the heating rate of the second heating stage is 1°C / min-10°C / min.

[0029] In some embodiments of the present invention, the calcination includes: the first heating stage: heating to T1 at a heating rate of ≥3°C / min; the second heating stage: heating to T2 at a heating rate of ≤2°C / min; the heat preservation stage: heat preservation for t1 hours in the temperature range of T2-10°C to T2+10°C; wherein, 600°C≤T1≤800°C, 900°C≤T2≤1100°C, 5h≤t1≤15h. Thus, when the above conditions are met, the energy density and air stability of the positive electrode material are maximized.

[0030] In some embodiments of the present invention, the positive electrode active material precursor includes:

[0031] Ni x2 Fe y2 Mn z2 Zn m2 O a H b ,

[0032] Among them, 0 <x2≤0.5,0<y2≤0.5,0<z2≤0.5,0≤m2≤0.2,1≤a≤2,0≤b≤2,x2+y2+z2+m2=1。

[0033] In some embodiments of the present invention, the D of the positive electrode active material precursor 50 The particle size is 5μm-6μm,

[0034] In some embodiments of the present invention, the particle size distribution of the positive electrode active material precursor is 1.1 < (D 90 -D 10 ) / D 50 <1.6.

[0035] In some embodiments of the present invention, the tap density of the positive electrode active material precursor is 1.50 g / cm 3 -1.80g / cm 3 .

[0036] In some embodiments of the present invention, the specific surface area of ​​the positive electrode active material precursor is 10m 2 / g-20m 2 / g.

[0037] In a third aspect of the present invention, the present invention provides a positive electrode plate, comprising the positive electrode active material described in the first aspect of the present invention.

[0038] In a fourth aspect of the present invention, the present invention provides a battery, comprising the positive electrode sheet described in the third aspect of the present application, so that the battery has excellent electrochemical performance.

[0039] In a fifth aspect of the present invention, the present invention provides an electrical device, comprising the battery described in the fourth aspect of the present invention.

[0040] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 is a SEM image of the positive electrode active material precursor prepared in Example 1 of the present application;

[0042] Figure 2 is a SEM image of the positive electrode active material prepared in Example 1 of the present application;

[0043] Figure 3 is the XRD pattern of the positive electrode active material precursor prepared in Example 1 of the present application;

[0044] Figure 4 is the XRD pattern of the positive electrode active material prepared in Example 1 of the present application;

[0045] Figure 5 It is the Fe element XPS graph of the positive electrode active material prepared in Example 1 and Comparative Example 1 of the present application before charging and after charging to 4.0V;

[0046] Figure 6 The 0.1C first-cycle charge-discharge curves of the positive electrode active materials prepared in Example 1 and Comparative Example 1 of the present application in the 2.0-4.15V voltage window are shown. DETAILED DESCRIPTION

[0047] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0048] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0049] In one aspect of the present invention, the present invention provides a positive electrode active material, wherein Fe 2+ The change in content Δn≥0.1, Δn=n1-n2; wherein n1 is the Fe content in the positive electrode active material before charging.2+ n2 is charged to 4.0V, the positive electrode active material Fe 2+ Content: Fe 2+ Content = Fe in positive electrode active material 2+ Amount of substance / (Fe in positive electrode active material 2+ Amount of substance + Fe in positive electrode active material 3+ amount of substance).

[0050] As an example, Δn may be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, etc. According to some other embodiments of the present invention, Δn≥0.15.

[0051] The inventors found that in the iron-containing layered oxide as the positive electrode active material, iron can provide the main capacity, and iron provides capacity through the change of valence state. When the above positive electrode active material Fe 2+ When the content changes Δn≥0.1, there is more Fe 2+ Convert to Fe 3+ , Fe 2+ The large content variation allows more electrons to be transferred during the charging process, increasing the capacity of the positive electrode active material and thereby increasing the energy density of the battery containing it.

[0052] In the present embodiment, XPS can be used to test the iron content of different valence states in the sodium positive electrode active material, and the XPSPEAK41 software can be used to fit and analyze the data to obtain Fe 2+ The content of n1 is measured before the positive electrode material is charged and discharged, and n2 is measured by XPS after the positive electrode active material is prepared into a sodium ion battery according to a conventional method and charged to 4V at a current of 0.1C. Furthermore, the tests n1 and n2 in this application are measured in the first 20 weeks of the positive electrode material cycle.

[0053] It can be understood that XPS, or X-ray Photoelectron Spectroscopy, is a technology used to analyze the chemical composition of the surface of materials.

[0054] In this application, the sodium positive electrode active material has more Fe during the process of charging to 4.0V. 2+ Convert to Fe 3+ , Fe 2 + The content changes greatly, and more electrons can be transferred during the charging process, thereby increasing the battery capacity.

[0055] According to an embodiment of the present invention, n1 is greater than 50%, for example, n1 can be 51%, 55%, 60%, 70%, 80%, 90%, 100%, etc., n1 is greater than 70%; more preferably, n1 is greater than 80%. 2+ High content, on the one hand, during the charging process, Fe 2+ / Fe 3+ The oxidation reaction transfers electrons to provide capacity. When charged to 4.0V, more Fe 2+ Oxidized to Fe 3+ , can transfer more electrons and provide more capacity; on the other hand, it can reduce O 2- / O - The oxidation potential of the material originally between 4.10 and 4.15 V is increased. 2- / O - The oxidation reaction occurs earlier at around 3.90V, providing more capacity in the 2.0-4.0V voltage range.

[0056] According to an embodiment of the present invention, the positive electrode active material includes:

[0057] Na a1 Ni x1 Fe y1 Mn z1 Zn m1 Ca q M p1 O2,

[0058] Among them, 0.90≤a1≤1.10, 0 <x1≤0.5,0<y1≤0.5,0<z1≤0.5,0<m1≤0.1,0≤q≤0.05,0<p1≤0.05;

[0059] M includes at least one of Cu, Ti, Mg, Sr, Sn, Sb, Zr, Nb, Y, W, and La.

[0060] As an example, a1 can be 0.90, 0.95, 1.0, 1.05, 1.10, etc.; x1 can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, etc.; y1 can be 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, etc.; z1 can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, etc.; m1 can be 0.01, 0.05, 0.1, 0.15, 0.2, etc.; q can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, etc.; p1 can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, etc.

[0061] By adjusting the proportion of Zn element in the composition of the positive electrode active material within a suitable range, the capacity of the positive electrode active material at low voltages (2.0 - 4.0V) can be significantly improved, and the average voltage can be raised, resulting in a significant increase in the energy density of the positive electrode active material. In addition, introducing Zn element into the positive electrode active material can make the average particle size of the fabricated positive electrode active material larger, and the particle size of the positive electrode active material increases more significantly with the increase of the Zn element content. The Zn element helps to improve the degree of single crystallization of the positive electrode active material particles and increase the tap density of the positive electrode active material.

[0062] When q and / or p1 is not equal to 0, that is, the positive electrode active material is doped with Ca and / or M. By introducing Ca doping, Ca can enter the sodium layer and the transition metal layer in the positive electrode active material to form a barrier to protect Na in the structure from contacting water and carbon dioxide in the air, thus improving the air stability of the positive electrode active material; further introducing a doping element M with an ionic radius larger than the main elements Ni, Fe, and Mn and controlling an appropriate doping amount can expand the layer spacing of the positive electrode active material, improve the rate performance, and alleviate the + structural changes caused during the insertion / extraction process and improve the structural stability of the positive electrode active material.

[0063] According to the embodiments of the present invention, x1 + y1 + z1 + m1 + q + p1 = 1.

[0064] According to the embodiments of the present invention, a1:(x1 + y1 + z1 + m1 + q + p1) = (0.90 - 1.05):1. For example, it can be 0.90:1, 0.95:1, 1.0:1, 1.05:1, etc. Preferably, a1:(x1 + y1 + z1 + m1 + q + p1) = (0.95 - 1.05):1; more preferably (0.97 - 1.03):1. Thus, the proportion of sodium ions to the sum of other metal ions is moderate, which can further improve the capacity of the positive electrode active material and then increase the energy density of the battery containing it.

[0065] According to the embodiments of the present invention, 0.01 < m1 ≤ 0.2. For example, m1 can be 0.01, 0.05, 0.1, 0.15, 0.2, etc. Preferably, 0.05 < m1 ≤ 0.1. By controlling the Zn content in the positive electrode active material within the above range, the capacity of the positive electrode active material at (2.0 - 4.0V) can be significantly improved, and the average voltage can be raised, resulting in a significant increase in the energy density of the positive electrode active material; and the Zn element helps to improve the degree of single crystallization of the positive electrode active material particles and increase the tap density of the positive electrode active material, further increasing the energy density.

[0066] According to an embodiment of the present invention, 0.01<q≤0.05, for example, it can be 0.01, 0.02, 0.03, 0.04, 0.05, etc. Thus, the calcium content in the positive electrode active material is controlled within the above range, which is further conducive to Ca entering the sodium layer and transition metal layer in the positive electrode active material, forming a barrier to protect Na in the structure from contacting water and carbon dioxide in the air, improving the air stability of the positive electrode active material, so that the battery containing it has excellent cycle performance.

[0067] According to an embodiment of the present invention, the ionic radius r of M>0.06nm, such as 0.065nm, 0.07nm, 0.08nm, 0.09nm, 0.1nm, 0.15nm, etc. The ionic radius of the M element is within the above range, which can expand the interlayer spacing of the positive electrode active material, improve the rate performance, and alleviate the Na + The structural changes caused during the insertion / extraction process improve the structural stability of the positive electrode active material, thereby improving the cycle performance of the battery containing it.

[0068] According to an embodiment of the present invention, the positive electrode active material is an O3 type sodium ion battery layered oxide, so that the capacity of the positive electrode active material is high, the compaction density of the positive electrode active material is improved, and the volume energy density of the manufactured battery is increased.

[0069] According to an embodiment of the present invention, the D of the positive electrode active material 50 The particle size is 3 μm-12 μm, for example, D 50 The particle size can be 3 μm, 5 μm, 7 μm, 9 μm, 10 μm, 12 μm, etc., preferably 4 μm-10 μm; more preferably 5 μm-8 μm. 50 When the particle size is controlled within the above range, both the short migration path of sodium ions and the small side reaction between the positive electrode active material and the electrolyte can be taken into account, thereby improving the cycle performance of the battery containing it.

[0070] In the present invention, D 50 The particle size refers to the particle size corresponding to when the cumulative volume distribution percentage reaches 50%, and is measured using a laser particle size analyzer (such as Malvern Master Size 3000) with reference to standard GB / T 19077-2016.

[0071] According to an embodiment of the present invention, the particle size distribution (K 90 )1.1<(D 90 -D 10 ) / D 50 <1.6, preferably 1.2<(D 90 -D 10 ) / D50 <1.4. For example, (D 90 -D 10 ) / D 50 It can be 1.11, 1.2, 1.3, 1.4, 1.5, 1.59, etc. Therefore, the particle size distribution of the positive electrode active material is wide, and it has higher compaction density and volume energy density.

[0072] Understandable, D 10 It refers to the particle size corresponding to the cumulative volume distribution percentage of the positive electrode active material reaching 10%, D 50 It refers to the particle size corresponding to when the cumulative volume distribution percentage of the positive electrode active material reaches 50%, D 90 It refers to the particle size corresponding to when the cumulative volume distribution percentage of the positive electrode active material reaches 90%. The above particle size can be measured using a laser particle size analyzer (such as Malvern Master Size 3000).

[0073] In a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned positive electrode active material. According to an embodiment of the present invention, the method comprises:

[0074] S100: taking a Na source, a cathode active material precursor, an optional Zn source, an optional Ca source, and an M source in a stoichiometric ratio and mixing them uniformly to obtain a mixed material, wherein the cathode active material precursor includes Fe.

[0075] According to an embodiment of the present invention, the Na source, Zn source, Ca source, and M source may be commercially available products.

[0076] As an example, the Na source includes at least one of sodium carbonate, sodium hydroxide, sodium nitrate and sodium oxide.

[0077] The Zn source includes at least one of ZnO, ZnCO3, ZnCl2, Zn3(PO4)2, ZnF2, ZnCl2, Zn(OH)2 and ZnSi.

[0078] The Ca source includes at least one of Ca oxide, Ca carbonate, Ca phosphate, Ca fluoride, Ca chloride, Ca hydroxide and Ca silicide.

[0079] The M source includes at least one of an oxide of M, a carbonate of M, a phosphate of M, a fluoride of M, a chloride of M, a hydroxide of M, and a silicide of M.

[0080] According to an embodiment of the present invention, the ratio of the amount of Na element to the sum of the amounts of Ni, Fe, Mn, Zn, Ca and M is 0.90-1.10, that is, n(Na) / [n(Ni)+n(Fe)+n(Mn)+n(Zn)+n(Ca)+n(M)]=0.90-1.10, for example, it can be 0.90, 0.95, 1.0, 1.05, 1.10, etc., preferably 0.97-1.03. When preparing the positive electrode active material, controlling the ratio of the amount of Na element to the sum of the amounts of Ni, Fe, Mn, Zn, Ca and M within the above range is beneficial to the prepared positive electrode active material. During the charging process to 4.0V, Fe 2+ The change in content △n ≥ 0.1 makes more Fe 2+ Convert to Fe 3+ , Fe 2+ The large content variation allows more electrons to be transferred during the charging process, increasing the capacity of the positive electrode active material and thereby increasing the energy density of the battery containing it.

[0081] According to an embodiment of the present invention, the positive electrode active material precursor includes:

[0082] Ni x2 Fe y2 Mn z2 Zn m2 O a H b ,

[0083] Among them, 0 <x2≤0.5,0<y2≤0.5,0<z2≤0.5,0≤m2≤0.2,1≤a≤2,0≤b≤2,x2+y2+z2+m2=1。

[0084] As an example, x2 can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, etc.; y2 can be 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, etc.; z2 can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, etc.; m2 can be 0, 0.01, 0.05, 0.1, 0.15, 0.2, etc.; a can be 1, 1.2, 1.4, 1.5, 1.7, 2, etc.; b can be 0, 0.5, 1, 1.5, 2, etc.

[0085] It can be understood that during the preparation of the positive electrode active material, Zn can be introduced when the positive electrode active material precursor is prepared (at this time m2≠0); or it can be not introduced when the positive electrode active material precursor is prepared, but when the Na source, the positive electrode active material precursor (at this time m2=0), optionally a Zn source, optionally a Ca source, and optionally an M source are mixed, the Zn source is added at the same time, and the mixture is calcined. Both preparation methods are within the scope of protection of the present application.

[0086] As an example, the zinc source compound is selected from at least one of ZnO, ZnCO3, ZnCl2, Zn3(PO4)2, ZnF2, ZnCl2, Zn(OH)2, and ZnSi.

[0087] According to an embodiment of the present invention, the positive electrode active material precursor can be prepared by the following method:

[0088] Prepare a mixed salt solution with a concentration of 1.0-3.0 mol / L of nickel salt, iron salt, manganese salt and zinc salt according to the molar ratio of Ni:Fe:Mn:Zn=x2:y2:z2:m2;

[0089] The mixed salt solution, the complexing agent and the alkaline aqueous solution are continuously synthesized into a precursor slurry of a multi-element positive electrode material positive electrode active material under the protection of argon, nitrogen or other inert atmosphere;

[0090] The positive electrode active material precursor slurry of the multi-element positive electrode material is filtered, washed and dried to obtain a positive electrode active material precursor.

[0091] According to an embodiment of the present invention, the D of the positive electrode active material precursor 50 The particle size is 5μm-6μm, for example, it can be 5μm, 5.3μm, 5.5μm, 5.8μm, 6μm, etc. By controlling the particle size of the positive electrode active material precursor within the above range, a positive electrode active material with a suitable particle size can be obtained, which can take into account both the short migration path of sodium ions and the small side reaction between the positive electrode active material and the electrolyte, thereby improving the cycle performance of the battery containing it.

[0092] According to an embodiment of the present invention, the particle size distribution (K 90 )1.1<(D 90 -D 10 ) / D 50 <1.6, for example, it can be 1.11, 1.2, 1.3, 1.4, 1.5, 1.59, etc., thereby, the particle size distribution of the positive electrode active material precursor is wide, and the corresponding particle size distribution of the prepared positive electrode active material is wide, so that the positive electrode active material has a higher compaction density and volume energy density.

[0093] According to an embodiment of the present invention, the tap density of the positive electrode active material precursor is 1.50 g / cm 3 -1.80g / cm 3 , for example, it can be 1.50 g / cm 3 , 1.55g / cm 3 , 1.60g / cm 3 , 1.65g / cm 3 , 1.70g / cm 3, 1.75g / cm 3 , 1.80g / cm 3 wait.

[0094] According to an embodiment of the present invention, the specific surface area of ​​the positive electrode active material precursor is 10m 2 / g-20m 2 / g. For example, it can be 10m 2 / g,12m 2 / g,15m 2 / g,17m 2 / g,20m 2 / g, etc.

[0095] S200: calcining the mixed material in an oxidizing atmosphere, crushing and sieving to obtain a positive electrode active material.

[0096] According to an embodiment of the present invention, the oxidizing atmosphere includes oxygen or air.

[0097] According to an embodiment of the present invention, the calcination temperature is 900°C-1100°C. For example, the calcination temperature may be 900°C, 950°C, 1000°C, 1050°C, 1100°C, etc.; thus, by making the calcination temperature within the above range, a positive electrode active material with higher purity, stable structure and high capacity can be formed, thereby improving the cycle performance and energy density of the battery containing the positive electrode active material.

[0098] According to an embodiment of the present invention, the calcination includes a first heating stage, a second heating stage and a heat preservation stage, and the difference between the heating rate of the first heating stage and the heating rate of the second heating stage is 1°C / min-10°C / min. For example, the difference between the heating rate of the first heating stage and the heating rate of the second heating stage is 1°C / min, 2°C / min, 5°C / min, 10°C / min, etc. In this way, the energy density and air stability of the obtained positive electrode active material can be maximized, thereby improving the energy density and cycle performance of the battery.

[0099] According to an embodiment of the present invention, the calcination comprises:

[0100] (a) First heating stage: heating to T1 at a first heating rate of ≥3°C / min;

[0101] (b) Second heating stage: heating to T2 at a second heating rate of ≤2°C / min;

[0102] (c) Insulation stage: Insulation within the temperature range of T2-10°C to T2+10°C for t1 hour;

[0103] Among them, T1 ranges from 600℃≤T1≤800℃; T2 is the first calcination temperature, 900℃≤T2≤1100℃; t1 is the heat preservation calcination time, 5h≤t1≤15h;

[0104] As an example, the heating rate of the first heating stage can be 3℃ / min, 5℃ / min, 8℃ / min, 10℃ / min, etc.; T1 can be 600℃, 650℃, 700℃, 750℃, 800℃, etc.; the heating rate of the second heating stage can be 0.5℃ / min, 1℃ / min, 1.5℃ / min, 2℃ / min, etc.; T2 can be 900℃, 950℃, 1000℃, 1050℃, 1100℃, etc., and t1 can be 5h, 8h, 10h, 15h, etc.

[0105] When the above conditions are met, the energy density and air stability of the positive electrode active material are maximally compatible.

[0106] In summary, the positive electrode active material obtained by the above method can further improve the energy density and rate performance of the material compared to the existing nickel-iron-manganese ternary material, and greatly improve the problems of poor air stability and low cycle life of the material.

[0107] In a third aspect of the present invention, the present invention provides a positive electrode sheet. According to an embodiment of the present invention, the positive electrode sheet comprises the positive electrode active material described in the first aspect of the present invention, or the positive electrode active material prepared by the method described in the second aspect.

[0108] According to an embodiment of the present invention, the positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on the positive electrode collector, the positive electrode active material layer includes the above-mentioned positive electrode active material, wherein the positive electrode collector can be a metal foil or a composite current collector (the metal material can be arranged on a polymer substrate to form a composite current collector), for example, the positive electrode collector can be an aluminum foil.

[0109] According to some embodiments of the present invention, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, or fluorine-containing acrylate resin.

[0110] According to some embodiments of the present invention, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers.

[0111] According to some embodiments of the present invention, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0112] It should be noted that the features and advantages described above for the positive electrode active material and the preparation method thereof are also applicable to the positive electrode plate and will not be described in detail here.

[0113] In a fourth aspect of the present invention, the present invention provides a battery. According to an embodiment of the present invention, the battery comprises at least one of the positive electrode sheets described in the third aspect.

[0114] As an example, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the separator is located between the positive electrode sheet and the negative electrode sheet. During the charge and discharge process of the battery, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0115] According to an embodiment of the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, wherein the negative electrode current collector can be a metal foil or a composite current collector (a metal material can be arranged on a polymer substrate to form a composite current collector), for example, the positive electrode current collector can be a copper foil.

[0116] According to some embodiments of the present invention, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, sodium titanate, etc.

[0117] According to some embodiments of the present invention, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.

[0118] According to some embodiments of the present invention, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0119] According to some embodiments of the present invention, the negative electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, and the binder are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0120] According to some further embodiments of the present invention, the negative electrode plate may include a metal sodium plate or a sodium alloy, such as a sodium-indium alloy.

[0121] According to some other embodiments of the present invention, there is no particular restriction on the type of the isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. As an example, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film without particular restriction. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different without particular restriction.

[0122] According to some other embodiments of the present invention, the type of electrolyte is not specifically limited and can be selected according to needs. For example, the electrolyte can be in a gel state or a fully solid state. According to some specific embodiments of the present invention, the electrolyte is an electrolyte solution, and the electrolyte solution includes a sodium salt and a solvent.

[0123] According to some specific embodiments of the present invention, the sodium salt may include at least one of sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bisoxalatoborate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethylsulfonate or sodium bis(trifluoromethylsulfonyl)imide.

[0124] According to some specific embodiments of the present invention, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, ethylene glycol dimethyl ether, methyl ethyl sulfone or diethyl sulfone.

[0125] In some embodiments of the present application, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0126] It should be noted that the above-mentioned features and advantages described for the positive electrode plate are also applicable to the solid-state battery and will not be repeated here.

[0127] In a fifth aspect of the present invention, the present invention provides an electric device. According to an embodiment of the present invention, the electric device includes the above-mentioned battery. According to an embodiment of the present invention, the electric device may include but is not limited to a mobile phone, a laptop computer, an electric vehicle, etc.

[0128] It should be noted that the features and advantages described above for the battery are also applicable to the electrical device and will not be repeated here.

[0129] Below, the embodiment of the present invention is described. The embodiment described below is exemplary, is only used to explain the present invention, and cannot be interpreted as limiting the present invention. If no specific technology or conditions are indicated in the embodiment, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments is not indicated, they are all conventional products that can be obtained commercially.

[0130] Example 1

[0131] S100: Dissolve nickel sulfate, iron sulfate, manganese sulfate and zinc sulfate in a molar ratio of 25:33:37:5 for nickel, iron, manganese and zinc elements to obtain a 2 mol / L mixed salt solution; dissolve sodium hydroxide into a precipitant solution with a concentration of 10 mol / L; dissolve ammonia water into a complexing agent solution with a concentration of 8 mol / L. 100L of the mixed salt solution, the precipitant solution and the complexing agent solution are introduced into the reactor in parallel at a temperature of 60°C and a pH value of 11.50, and then under the protection of a nitrogen atmosphere, the crystal growth of the precipitate is continuously controlled in an overflow device until the average particle size of the particles grows to 5μm. The precursor slurry is filtered and washed, and the filter cake is dried at 120°C and sieved to obtain a multi-element precursor A. The particle size distribution of the precursor is K 90 =(D 90 -D 10 ) / D 50 =1.3.

[0132] S200: The multi-precursor A, CaO, yttrium oxide and Na2CO3 prepared in S1 are mixed in a molar ratio of Na / (Ni+Fe+Mn+Zn+Ca+Y)=1.01:1, wherein the molar ratios of Na / Ca=1.01:0.02 and Na / Y=1.01:0.02. The temperature is first increased to 700°C at a heating rate of 3°C / min in an oxidizing atmosphere, and then increased to 1000°C at a heating rate of 1°C / min. The mixture is kept warm for 15 hours for mixing. After cooling, crushing and screening, an O3 type single crystal positive electrode active material is obtained.

[0133] Example 2

[0134] Except that the molar ratio of nickel, iron, manganese and zinc in step S100 is adjusted to 25:33:35:7, the other preparation methods and parameters are the same as those in Example 1.

[0135] Example 3

[0136] Except that yttrium oxide is replaced by magnesium oxide in step S200, the rest of the preparation method and parameters are the same as those in Example 1.

[0137] Example 4

[0138] Except that the molar ratio of Na / Ca is adjusted to 1.01:0.05 in step S200, the remaining preparation methods and parameters are the same as those in Example 1.

[0139] Example 5

[0140] Except that the molar ratio of Na / Y is adjusted to 1.01:0.05 in step S200, the remaining preparation methods and parameters are the same as those in Example 1.

[0141] Example 6

[0142] Except for step S100 in which the average particle size of the particles is grown to 8 μm, the other preparation methods and parameters are the same as those in Example 1.

[0143] Example 7

[0144] Except that yttrium oxide is replaced by aluminum oxide in step S200, the rest of the preparation method and parameters are the same as those in Example 1.

[0145] Example 8

[0146] Except that the molar ratio of nickel, iron, manganese and zinc in step S100 is adjusted to 25:33:41:1, the other preparation methods and parameters are the same as those in Example 1.

[0147] Example 9

[0148] Except that calcium oxide is not added in step S200, that is, the molar amount of calcium is 0, the rest of the preparation method and parameters are the same as those in Example 1.

[0149] Example 10

[0150] Except for step S100 in which the average particle size of the particles is grown to 14 μm, the other preparation methods and parameters are the same as those in Example 1.

[0151] Embodiment 11

[0152] Except for the precursor particle size distribution K in step S100 90 =(D 90 -D 10 ) / D50 =0.8, the other preparation methods and parameters are the same as those in Example 1. The particle size distribution of the precursor is different from that in Example 1 by the following adjustment: without passing through the overflow device, the prepared solution is added to the reactor until the reactor is full, and when the precursor particle size in the reactor grows to meet the requirements, all the materials in the reactor are discharged.

[0153] Example 12

[0154] Except that the molar ratio of nickel, iron, manganese and zinc in step S100 is adjusted to 25:33:27:15, the other preparation methods and parameters are the same as those in Example 1.

[0155] Embodiment 13

[0156] Except that the molar ratio of nickel, iron, manganese and zinc in step S100 is adjusted to 25:33:32:10, the other preparation methods and parameters are the same as those in Example 1.

[0157] Comparative Example 1

[0158] Except that the molar ratio of nickel, iron, manganese and zinc in step S100 is adjusted to 25:33:42:0 (ie, zinc sulfate is not added), the remaining preparation methods and parameters are the same as those in Example 1.

[0159] The compositions of the positive electrode active material precursors and positive electrode active materials prepared in the above examples and comparative examples are specifically shown in Table 1.

[0160] Table 1

[0161]

[0162] (1) Morphology test

[0163] The present invention tests the scanning electron microscope images of the positive electrode active material precursor and the O3 type single crystal positive electrode active material prepared in the above embodiments and comparative examples, and provides the SEM images of the positive electrode active material precursor and the O3 type single crystal positive electrode active material prepared in Example 1 as an example. The results are as follows: Figure 1 and Figure 2 As shown, from Figure 1 It can be seen that the particle size distribution of the positive electrode active material precursor is wide and the particle surface is dense; Figure 2 It can be seen that the surfaces of large and small single crystal particles of the positive electrode active material are smooth, and the particle size distribution is wide. Small particles are filled between large particles, and have good grading performance.

[0164] (2) Physical property test

[0165] The present invention tests the XRD patterns of the positive electrode active material precursor and the O3 type single crystal positive electrode active material in the above-mentioned embodiments and comparative examples, and provides the XRD patterns of the positive electrode active material precursor and the O3 type single crystal positive electrode active material prepared in Example 1 as an example. The results are as follows: Figure 3 and Figure 4 As shown, from Figure 3 It can be seen that the phase of the positive electrode active material precursor is (Ni 0.25 Fe 0.33 Mn 0.37 Zn 0.05 )O(OH); Figure 4 It can be seen that the physical phase of the sodium-ion single crystal positive electrode active material of Example 1 of the present invention is a sodium-ion O3-type layered oxide (Na 1.01 Ni 0.240 Fe 0.317 Mn 0.355 Zn 0.048 Ca 0.020 Y 0.020 O2).

[0166] The present invention also conducts XPS test on the iron element of the O3 type single crystal positive electrode active material in the above-mentioned embodiment and comparative example, and provides exemplary XPS test fitting images of the Fe element of the sodium positive electrode active material before the first charge and when charged to 4.0V in embodiment 1 and comparative example 1. The results are as follows Figure 5 shown.

[0167] contrast Figure 5 a and Figure 5 c It can be seen that Fe in Example 1 2+ The amount of the substance is much higher than that of Fe in Comparative Example 1. 2+ The amount ratio of the substance is further compared with the Fe element XPS images of the positive electrode active material of Example 1 before charging and after charging to 4.0V ( Figure 5 a, b), and Fe element XPS images of the positive electrode active material of Comparative Example 1 before charging and after charging to 4.0 V ( Figure 5 c, d), it can be found that the positive electrode active material of Example 1 has more Fe before charging and after charging to 4.0V. 2+ Oxidized to Fe 3 + , a process that can transfer more electrons to provide capacity.

[0168] (3) Hygroscopicity test

[0169] The O3 type single crystal positive electrode active materials prepared in the above examples and comparative examples were simultaneously exposed to air with a relative humidity of 45% for 0 to 6 hours. The precise moisture and residual alkali parameters thereof are specifically shown in Table 2.

[0170] Table 2

[0171]

[0172] It can be seen from the above results that the positive electrode active material, compared with Example 9 without Ca doping, contains Ca doping in other examples, all show lower initial moisture, water-measured Na2CO3 and alcohol-measured NaOH content, and when exposed to air for a long time, the degree of water absorption, Na2CO3 and NaOH conversion are lower. The samples with Ca doping within the preferred range are much lower than the samples without Ca doping in terms of moisture increment (Δ moisture (%)) and residual alkali conversion rate (Δ (Na2CO3 + NaOH) (%)), showing better air stability.

[0173] Where, Δ moisture = moisture (t x -t1) / moisture t1, 1≤x≤6;

[0174] Δ(Na2CO3+NaOH)=(Na2CO3(t x -t1)) / Na2CO3(t1)+(NaOH(t x -t1) / NaOH(t1)).

[0175] (4) Particle size distribution K 90 and median particle size D 50 , compaction density and average particle size test

[0176] The present invention tests the particle size distribution K of the positive electrode active material precursor prepared in the above embodiment and comparative example. 90 and median particle size D 50 , and the compaction density of the prepared O3 type single crystal positive electrode active material, the specific test results are shown in Table 3.

[0177] Table 3

[0178]

[0179] It can be seen from the above results that the K of the positive electrode active material precursor obtained by the method described in this application is 90 All are greater than 1 (except for K in Example 11 90 Less than 1), the particle size distribution is wide. Figure 1 It can be further seen that the size distribution of the positive electrode active material precursor is relatively wide; and the morphology of the positive electrode active material produced is also a wide distribution of size particles, such as Figure 2 shown.

[0180] By comparing the examples and comparative examples in Table 3, it can be seen that when the particle size distribution K of the positive electrode active material precursor is 90 When the value range of is within the preferred range, the sintered positive electrode active material can still maintain a wide particle size distribution and has a high compaction density and volume energy density (corresponding to Table 5). 90 Outside the preferred range, the prepared positive electrode active material exhibits a lower compaction density. In addition, the present application measures the average particle size D of the above embodiments and comparative examples by using LIBMAS single crystal particle size measurement software. a By comparing Examples 1, 2, and 8 with Comparative Example 1, it can be found that the introduction of the Zn element can make the average particle size of the positive electrode material larger, and the particle size increases more with the increase of the Zn element content. The Zn element helps to improve the single crystal degree of the particles and improve the compaction density of the material.

[0181] The expression of the sodium positive electrode active material of the present invention is as follows:

[0182] Na a1 (Ni x1 Fe y1 Mn z1 Zn m1 Ca q M p1 )O2

[0183] (5) Ionic radius of M, doping ratio, 2θ(003) value, n1 and Δn test of positive electrode active materials

[0184] The ionic radius (r) and doping ratio (p1 / (x1+y1+z1+m1+q+p1)) of the doping element M used in the positive electrode materials of the embodiments and comparative examples were further statistically analyzed, and the 2θ(003) value of the positive electrode active material was tested; in addition, the amount of iron element in the O3-type single crystal positive electrode active material in the above embodiments and comparative examples was tested by XPS test, and the data was fitted and analyzed using XPSPEAK41 software to characterize Fe 2+ The proportion of Fe in the sodium positive electrode active material 2+ / (Fe2 + +Fe 3+ )), as shown in Table 4.

[0185] Table 4

[0186]

[0187] Comparing Example 1 and Example 7, it can be seen that the doping amount of M in the two samples is consistent, but the doping element M and its ion radius in Example 7 are not within the preferred range, and the 2θ(003) value of the positive electrode active material made thereof is larger, showing a smaller interlayer spacing; Comparing Example 1 and Comparative Example 1, it can be seen that the Fe in Example 1 containing the Zn element is 2+ The proportion is much higher than that of Fe in Example 1 without Zn element. 2+ Proportion.

[0188] The above results show that by doping with an element M with a large ion radius (r>0.06nm) and regulating the M doping amount within the preferred range, the interlayer spacing of the positive electrode material can be expanded, which is expected to alleviate the Na + The structural changes caused by the embedding / extraction process improve the structural stability of the material. In addition, the Zn-based positive electrode material, the initial Fe 2+ Higher, which is conducive to the passage of Fe during charging 2+ / Fe 3+ The oxidation reaction transfers more electrons, providing more capacity.

[0189] (6) Electrochemical performance testing of positive electrode active materials and batteries

[0190] Battery preparation method:

[0191] The positive electrode active material prepared in each example, acetylene black and polyvinylidene fluoride (PVDF) were mixed with an appropriate amount of N-methylpyrrolidone (NMP) in a mass ratio of 95:3:2 to form a uniform slurry, coated on an aluminum foil and dried at 120°C for 12 hours, and then stamped into a positive electrode sheet with a diameter of 12 mm and a thickness of 120 μm using a pressure of 100 MPa, wherein the loading amount of the positive electrode material was 15 mg / cm 2 .

[0192] Assemble the battery: In an Ar glove box with water and oxygen content less than 5ppm, assemble the positive electrode, separator, negative electrode and electrolyte into a 2025 button battery and leave it for 6 hours. The negative electrode uses a metal sodium sheet with a diameter of 17mm and a thickness of 1mm; the separator uses a Celgard 2325 porous membrane with a thickness of 25μm; the electrolyte uses an equal mixture of 1mol / L NaPF6, ethylene carbonate (EC) and diethyl carbonate (DEC).

[0193] Performance Testing Methods

[0194] The button cell was electrochemically tested at 25°C using the Xinwei battery test system, and the charge and discharge current density at 0.1C was 140mA / g:

[0195] 1. 2.0-4.0V, 0.1C first charge and discharge specific capacity test method

[0196] The prepared button cell was subjected to charge and discharge tests at 25°C, 2.0-4.0V, and 0.1C to evaluate the 0.1C first charge and discharge specific capacity of the material.

[0197] 2. Average voltage test method for positive electrode active materials

[0198] The prepared button cell was subjected to charge and discharge tests at 25°C, 2.0-4.0V, and 0.1C to evaluate the material's 0.1C first discharge specific energy and discharge specific capacity, and the average voltage was calculated, namely: discharge specific energy / discharge specific capacity

[0199] 3. Rate performance test method

[0200] The prepared button cell was cycled twice at 25°C, 2.0-4.0V, and 0.1C, and then cycled once at 0.2C, 0.33C, 0.5C, and 1C, respectively. The rate performance of the multi-electrode material was evaluated by the ratio of the 0.1C first discharge specific capacity to the 1C discharge specific capacity; wherein the 0.1C first discharge specific capacity is the discharge specific capacity of the button cell in the first cycle, and the 1C discharge specific capacity is the discharge specific capacity of the button cell in the sixth cycle.

[0201] 4. Cyclic performance test method

[0202] The prepared button cell was cycled twice at 25°C, 2.0-4.0V, and 0.1C, and then cycled at 1C for 80 weeks to evaluate the capacity retention of the material.

[0203] 5. Volume energy density test method

[0204] The volume energy density can be obtained by multiplying the 0.1C discharge specific capacity, average voltage and compaction density corresponding to each example in Table 3 obtained by the above methods 1 and 2.

[0205] The test results are shown in Table 5.

[0206] Table 5

[0207]

[0208] According to the data in Table 5, by comparing Examples 1 and 2 with Comparative Example 1, it can be seen that when the Zn content in the positive electrode active material is within the preferred range, it can exert a higher charge and discharge capacity and average voltage at 2.0-4.0V, and the energy density is higher. By comparing Example 1 with Example 7 and combining the data in Tables 4 and 5, it can be seen that the introduction of a doping element M with a large ion radius (r>0.06nm) and satisfying that the M doping amount is within the preferred range can expand the interlayer spacing of the positive electrode material, improve the rate performance, and alleviate the Na + The structural changes caused during the embedding / ejection process improve the structural stability and cyclic stability of the material.

[0209] Comparing Example 1 with Examples 10 and 6, it can be seen that when the particle size distribution K of the positive electrode active material precursor is 90 and D 50 When the particle size is within the preferred range, the compaction density of the positive electrode material is higher and the volume energy density is higher. a If the value is too large, the compaction is reduced and the energy density is lower than that of Examples 1 and 6.

[0210] Comparing Example 1 with Example 12, the Zn content is too high, 0.15, and the Fe 2+ The content increase is not large, and the others are the same as Example 1. The volume energy density does not change much relative to Example 1, but being too high will lead to rapid cycle decay.

[0211] The present invention also tests the sodium ion battery positive electrode active material prepared in the above Example 1 and Comparative Example 1, and the 0.1C first week charge and discharge curve in the 2.0-4.15V voltage window is as follows: Figure 6 As shown, by comparing the charge and discharge curves of Example 1 and Comparative Example 1, it can be seen that after Zn addition, the charge curve will have a new inflection point at 3.05V ( Figure 6 middle red circle), and the slope becomes slower (Fe 2+ / Fe 3+ Oxidation reaction), there will be an upward inflection point at around 3.90V (O 2- / O - Oxidation reaction), combined with the initial Fe 2+ / (Fe 2+ +Fe 3+ ) content, indicating that Zn doping can make the initial material Fe 2+ Increase, during the charging process through Fe 2+ / Fe 3+ The oxidation reaction transfers more electrons and provides more capacity; on the other hand, it can reduce O 2- / O -The oxidation potential of the material originally between 4.10 and 4.15 V is increased. 2- / O - The oxidation reaction occurs in advance at about 3.90V, providing more capacity in the voltage range of 2.0-4.0V. Therefore, the capacity of Example 1 is greatly improved compared with Comparative Example 1 at 2.0-4.0V.

[0212] It can be seen from the above results that in the sodium ion battery positive electrode material provided by the present invention, when the particle size distribution K 90 and D 50 The Zn-based multi-element continuous process precursor within the preferred range is mixed with the first dopant Ca and the second dopant M (r>0.06nm) in a preferred doping ratio and calcined to obtain a positive electrode material with higher energy density and rate performance, and greatly improves the problems of poor air stability and low cycle life of the material.

[0213] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0214] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A positive electrode active material, characterized in that: The Fe in the positive electrode active material 2+ Change in content Δn≥0.1, Δn=n1-n2; Wherein, n1 is the Fe content in the positive electrode active material before charging. 2+ n2 is charged to 4.0V, the positive electrode active material Fe 2+ content; Fe 2+ Content = Fe in positive electrode active material 2+ Amount of substance / (Fe in positive electrode active material 2+ Amount of substance + Fe in positive electrode active material 3+ amount of substance); The positive electrode active material comprises: So a1 Ni x1 Feb y1 Mr z1 Zn m1 Approx q M p1 O2, Among them, 0.90≤a1≤1.10, 0 <x1≤0.5,0<y1≤0.5,0<z1≤0.5,0<m1≤0.1,0≤q≤0.05,0<p1≤0.05; M includes at least one of Cu, Ti, Mg, Sr, Sn, Sb, Zr, Nb, Y, W and La, a1: (x1+y1+z1+m1+q+p1)=(0.90-1.05):

1.

2. The positive electrode active material according to claim 1, characterized in that Δn≥0.

15.

3. The positive electrode active material according to claim 1, characterized in that n1 is greater than 50%.

4. The positive electrode active material according to claim 1, characterized in that n1 is greater than 70%.

5. The positive electrode active material according to claim 1, characterized in that n1 is greater than 80%.

6. The positive electrode active material according to claim 1, characterized in that a1: (x1+y1+z1+m1+q+p1)=(0.95-1.05):

1.

7. The positive electrode active material according to claim 1, characterized in that a1: (x1+y1+z1+m1+q+p1)=(0.97-1.03):

1.

8. The positive electrode active material according to claim 1, characterized in that 0.01<m1≤0.1。 9. The positive electrode active material according to claim 1, characterized in that 0.05<m1≤0.1。 10. The positive electrode active material according to claim 1, characterized in that 0.01<q≤0.05。 11. The positive electrode active material according to claim 1, characterized in that The ionic radius of M is r>0.06nm.

12. The positive electrode active material according to claim 1, characterized in that The positive electrode active material is an O3 type sodium ion battery layered oxide.

13. The positive electrode active material according to claim 1 or 2, characterized in that: The positive electrode active material D 50 The particle size is 3μm-12μm.

14. The positive electrode active material according to claim 1 or 2, characterized in that: The positive electrode active material D 50 The particle size is 4μm-10μm.

15. The positive electrode active material according to claim 1 or 2, characterized in that: The positive electrode active material D 50 The particle size is 5μm-8um.

16. The positive electrode active material according to claim 1 or 2, characterized in that: The particle size distribution of the positive electrode active material is 1.1<(D 90 -D 10 ) / D 50 <1.

6.

17. The positive electrode active material according to claim 1 or 2, characterized in that: The particle size distribution of the positive electrode active material is 1.2<(D 90 -D 10 ) / D 50 <1.

4.

18. A method for preparing the positive electrode active material according to any one of claims 1 to 17, characterized in that: include: A Na source, a cathode active material precursor, an optional Zn source, an optional Ca source, and an M source are mixed uniformly according to a stoichiometric ratio to obtain a mixed material, wherein the cathode active material precursor includes Fe; calcining the mixed material in an oxidizing atmosphere, crushing and sieving to obtain a positive electrode active material; The calcination includes a first heating stage, a second heating stage and a heat preservation stage, and the difference between the heating rate of the first heating stage and the heating rate of the second heating stage is 1°C / min-10°C / min.

19. The method according to claim 18, characterized in that The ratio of the amount of substance of the Na element to the sum of the amounts of substance of Ni, Fe, Mn, Zn, Ca and M is 0.90-1.

10.

20. The method according to claim 18, characterized in that The ratio of the amount of substance of the Na element to the sum of the amounts of substance of Ni, Fe, Mn, Zn, Ca and M is 0.97-1.

03.

21. The method according to claim 18, characterized in that The calcination temperature is 900°C-1100°C.

22. The method according to claim 18, characterized in that The calcination comprises: The first heating stage: heating to T1 at a heating rate of ≥3℃ / min; The second heating stage: heating to T2 at a heating rate of ≤2℃ / min; Insulation stage: Insulation within the temperature range of T2-10℃ to T2+10℃ for t1 hour; Among them, 600℃≤T1≤800℃, 900℃≤T2≤1100℃, 5h≤t1≤15h.

23. The method according to claim 18, characterized in that The positive electrode active material precursor comprises: No x2 Fe y2 Mn z2 Zn m2 ABOUT a H b , Among them, 0 <x2≤0.5,0<y2≤0.5,0<z2≤0.5,0≤m2≤0.2,1≤a≤2,0≤b≤2,x2+y2+z2+m2=1。 24. The method according to any one of claims 18 to 23, characterized in that The positive electrode active material precursor D 50 The particle size is 5μm-6μm.

25. The method according to any one of claims 18 to 23, characterized in that The particle size distribution of the positive electrode active material precursor is 1.1<(D 90 -D 10 ) / D 50 <1.

6.

26. The method according to any one of claims 18 to 23, characterized in that The tap density of the positive electrode active material precursor is 1.50 g / cm 3 -1.80g / cm 3 .

27. The method according to any one of claims 18 to 23, characterized in that The specific surface area of ​​the positive electrode active material precursor is 10m 2 / g-20m 2 / g.

28. A positive electrode plate, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 17.

29. A battery, characterized in that: Including the positive electrode sheet as described in claim 28.

30. An electrical equipment, characterized in that: Comprising the battery of claim 29.

Citation Information

Patent Citations

  • Positive electrode material, preparation method thereof and application of positive electrode material in sodium-ion battery

    CN116799186A

  • High-stability sodium ion battery positive electrode material as well as preparation method and application thereof

    CN118198308A

Cited By

  • Positive electrode active material and preparation method therefor, positive electrode sheet, battery and electric device

    EP4718537A1